Subfunctionalization of expression and peptide domains following the ancient duplication of the proopiomelanocortin gene in teleost fishes - De Souza, F.S.J. (2005)
The proopiomelanocortin gene (POMC) encodes several bioactive peptides, including adrenocorticotropin hormone, α-, β-, and γ-melanocyte-stimulating hormone, and the opioid peptide β-endorphin, which play key roles in vertebrate physiology. In the human, mouse, and chicken genomes, there is only one POMC gene. By searching public genome projects, we have found that Tetraodon (Tetraodon nigroviridis), Fugu (Takifugu rubripes), and zebrafish (Danio rerio) possess two POMC genes, which we called POMCα and POMCβ, and we present phylogenetic and mapping evidence that these paralogue genes originated in the whole-genome duplication specific to the teleost lineage over 300 MYA. In addition, we present evidence for two types of subfunction partitioning between the paralogues. First, in situ hybridization experiments indicate that the expression domains of the ancestral POMC gene have been subfunctionalized in Tetraodon, with POMCα expressed in the nucleus lateralis tuberis of the hypothalamus, as well as in the rostral pars distalis and pars intermedia (PI) of the pituitary, whereas POMCβ is expressed in the preoptic area of the brain and weakly in the pituitary PI. Second, POMCβ genes have a β-endorphin segment that lacks the consensus opioid signal and seems to be under neutral evolution in tetraodontids, whereas POMCα genes possess well-conserved peptide regions. Thus, POMC paralogues have experienced subfunctionalization of both expression and peptide domains during teleost evolution. The study of regulatory regions of fish POMC genes might shed light on the mechanisms of enhancer partitioning between duplicate genes, as well as the roles of POMC-derived peptides in fish physiology.